Peptides and astroglia improve the regenerative capacity of alginate gels in the injured spinal cord - Schackel, Thomas; Günther, Manuel Ingo; Liu, Shengwen; Sandner, Beatrice; Puttagunta, Radhika; Weidner, Norbert; Blesch, Armin (Tissue engineering, 2019)
Anisotropic alginate hydrogels with microchannels can provide a substrate for cotransplanted cells and for axons in the injured spinal cord by physically guiding regenerating axons across a lesion....